The Effect of Avicennia marina Fruit Flour as a Wheat Flour Subtitution on the Quality and Fiber Enhancement in Crackers - Nanda Ghaluh Ary Nashir; Juni Triastuti; Dwitha Nirmala (Journal of Marine and Coastal Science, 2022)
Avicennia marina is a plant that is commonly found in coastal areas. Avicennia marina fruit is known to have high carbohydrate and crude fiber content so that it has great potential as an alternative food ingredient that is able to meet the nutritional needs of the body. The purpose of the study was to of Avicennia marina fruit flour on the quality of crackers and its effect on the crude fiber content of crackers and to determine the best formulation for substitution of Avicennia marina fruit flour on crackers. The research uses experimental method with 5 different substitution treatments (0, 25, 30, 35 and 40%). Parameters observed were water content, ash content, protein content, crude fiber, hardness, organoleptic and yield content. The results showed that the best treatment was found in the substitution treatment of 25% Avicennia marina fruit flour with a moisture content, ash, protein, crude fiber, hardness of texture and yield are 3.18%, 2.56%, 6.75%, 3.39%, 42.18 N and 67.62%, respectively. The organoleptic results of the best treatment showed that organoleptic values included texture, taste, flavor and color are accepted by the panelists.